Utveckling av kontaktorgan till terrängdrönare - Rånman, Henrik (2015)
The ground contact organs that are used in forestry today have seen little change during the last decades and cannot be developed further to such an extent that all the inherent problems with these solutions can be avoided. The forest is a very demanding terrain that varies a lot and the machines that traffic such lands have to be well adapted for a variety of different obstacles and ground conditions. At the same time the pressure from the society on industries to become more environmentally friendly and leave a smaller mark on the planet is increasing. This is the fact in the forestry industry as well where ground damage is a serious problem that can have devastating consequences on the environment. To try to solve these issues the Swedish University of Agricultural Sciences have identified a possibility to use the advanced technology that is available today and the possibilities of active control through the use of computers to develop a new contact organ that would be more adaptable, have better terrain accessibility and produce less ground damage. This technology will then be evaluated through testing of the developed contact organ that will be added to a machine platform that was developed during an earlier student project in collaboration with Luleå University of Technology. This master’s thesis has involved a product development process from the planning phase to a detailed design of this contact organ. The finished result is a contact organ that with the help of hydraulics combines both active controls, through the use of on board computers with advanced control systems, and a passive damping that helps with obstacles and improves the terrain performance. The active control enables changes to the contact organs geometry in order to adapt to different terrain situations and increase productivity, improve driver comfort and reduce ground damage. Validerat; 20150610 (global_studentproject_submitter)